Plan de marketing social para la prevención de la diabetes, cantón Quevedo, año 2014. - Vinces Calle, Erika Elizabeth (2015)
This social marketing plan was reflected in Canton Quevedo, Los Rios Province, Ecuador, during the second half of 2014. The overall objective was to design a social marketing plan for the prevention of diabetes in the canton Quevedo. Chapter I. The contextual framework of the research is presented and the subject under study is introduced. Here's the questions of research, diagnosis, prognosis, and the systematization and operationalization of the main problem also arises: Does the implementation of the social marketing plan for the prevention of diabetes will help prevent the disease from growing among residents Quevedo town population? Also, in this chapter the general and specific objectives of the research, as well as the assumptions and their operation are presented. Chapter II. Includes the theoretical frame work of the research. Here the theoretical, legal foundations and basic concepts related to social marketing and diabetes are cited. Chapter III. Detail materials and methods and types of research that were used in the field research. Sources of information and expected results as well as the population, the sample under study and the methodological procedure is also included. In chapter IV. Results and discussion of research, summarized in tables and graphs are presented analyzed. This chapter includes discussion with a researcher par.....